Role of cooperatives in Indian Horticulture sector - Singh, Vikram; Shekhawat, Ravindra Singh; Sharma, Akriti (Indian Horticulture, 2022)
The cooperatives played an important role in horticulture sector by providing marketing and distribution network along with credit and inputs to the farmers, which supplemented the efforts of the state and private sector. The brand image along with community guidelines of these co-operatives helps the farmer in procurement, price/value fixation, limiting the post-harvest losses, mental and social support; as well stability in the market as well as in profession. The National Cooperative Development Corporation (NCDC) is major organization in the country which is meant for promoting, developing and financing post-harvest activities through cooperatives in agriculture and allied sectors. A new ministry with the name of Ministry of Cooperation under the Government of India has recently formed (July 2021) to provide a separate administrative, legal and policy framework for strengthening the cooperative movement in the country. The cooperative scenario is developing in the country with the efforts of growers and the government due to the realization of its enormous potential for socio-economic upliftment of its member and overall community.